PERFORMANCE-BASED BUDGETING EVALUATION IN BONTANG REGIONAL CIVIL SERVICE AGENCY - Fajar Apriani (Spirit Publik: Jurnal Administrasi Publik, 2015)
The demands of democratization that becoming a global phenomenon that demands the centrality of transparency and accountability in the government sector, including in financial management scope, creating government budgeting management reform in order to increases public participation and increases rule of law in the field of financial aspect, while increasing government performance. Output and outcomes become successive indicator of budgeting implementation by budget user unit. The application of budget performance in financial management of each unit become a curbing expenditure that give priority to the achievement of the results of the planned and allocated input for the execution of the duties and functions of the organization. So basically, the budget performance linking expenditures with results with the benchmarks on the performance of the organization. Key words: Performance budget, public sector budgeting, transparency and accountability, budgeting reform.